The Development of Mobilizing Educational Resource of Small Schools Under Suratthani Primary Educational Service Area Office 2 - Yongrath, Papatsara; Pechrpuang, Sopon; Boonchit, Yanisa (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were: 1) to investigate problems of educational resource mobilization in small schools; 2) to develop a model for educational resource mobilization in small schools; and 3) to examine the appropriateness and feasibility of educational resource mobilization in small schools under Suratthani Primary Educational Service Area Office 2.The research consisted of 3 steps: step 1; investigate problems in mobilizing educational resources in small schools. The sample group consisted of 63 small school administrators. The confidence level was 0.91; step 2: develop a model for mobilizing educational resources in small schools and assess the content validity of the model by 5 experts; and step 3: examine the appropriateness and feasibility of the educational resource mobilization model in small schools. The sample group who provided important information consisted of 16 small school administrators. The confidence values were 0.90 and 0.96. The data were analyzed by using basic statistics which were mean and standard deviation. The results of the research were as follows: 1) Problems in mobilizing educational resources in small schools were overall at a high level. Sorted in order are human resources, followed by media resources, materials and equipment, and budget resources. 2) The results of developing of a model for mobilizing educational resources in small schools were categorized in five components, 23 indicators. The five components consisted of (1) educational resource mobilization process/steps, (2) educational resource mobilization methods, (3) types of educational resources, (4)educational resource mobilization strategies, and (5) success conditions. 3) The results of examining the appropriateness and feasibility of educational resource mobilization models in small schools were overall at the highest level. In addition, the possibility of a model for mobilizing educational resources in schools were overall at a high level.